Facial Contrast Is a Cross-Cultural Cue for Perceiving Age - Porcheron, Aurélie; Mauger, Emmanuelle; Soppelsa, Frédérique; Liu, Yuli; Ge, Liezhong; Pascalis, Olivier; Russell, Richard; Morizot, Frédérique (Frontiers in Psychology, 2017)
Age is a fundamental social dimension and a youthful appearance is of importance for many individuals, perhaps because it is a relevant predictor of aspects of health, facial attractiveness and general well-being. We recently showed that facial contrast – the color and luminance difference between facial features and the surrounding skin- is age-related and cue to age perception of Caucasian women. Specifically, aspects of facial contrast decrease with age in Caucasian women, and Caucasian female faces with higher contrast look younger (Porcheron et al, 2013). Here we investigated faces of other ethnic groups and raters of other cultures to see whether facial contrast is a cross-cultural youth related attribute. Using large sets of full face color photographs of Chinese, Latin American and black South African women, aged 20 to 80, we measured the luminance and color contrast between the facial features (the eyes, the lips and the brows) and the surrounding skin. Most aspects of facial contrast that were previously found to decrease with age in Caucasian women were also found to decrease with age in the other ethnic groups. Though the overall pattern of changes with age was common to all women, there were also some differences between the groups. In a separate study, individual faces of the 4 ethnic groups were perceived younger by French and Chinese participants when the aspects of facial contrast that vary with age in the majority of faces were artificially increased, but older when they were artificially decreased. Altogether these findings indicate that facial contrast is a cross-cultural cue to youthfulness. Because cosmetics were shown to enhance facial contrast, this work provides some support for the notion that a universal function of cosmetics is to make female faces look younger.